Bertahan dalam Penderitaan: Studi Eksegesis 2 Timotius 4:1-8 - Yabes, Panuel (Student Evangelical Journal Aiming At Theological Interpretation, 2024)
In 2 Timothy 4:1-8, Paul reminds Timothy of the importance of enduring suffering as a minister of the Lord, emphasizing that before God and Christ Jesus, who will judge life and death, everyone must be faithful in preaching the Word. Paul encouraged Timothy to remain steadfast in spite of challenges and rejection, and reminded him that suffering is part of the call to ministry. He emphasized that with determination and courage, Timothy should carry out his duties, for in the end, faith maintained will result in the crown of righteousness promised by God to everyone who loves Him. In several passages in the Bible, including 2 Timothy 1:8, 2:3, and 3:11, Paul reminds us that suffering is an integral part of the Christian life, where every believer is called to bear the cross. This suffering is not only a challenge, but also a proof of unwavering faith in Christ, demonstrating commitment and faithfulness in following the gospel. Thus, the reality of suffering becomes a sign that one is truly following the call of Christ in his or her life